EXPLORING TEACHER MOTIVATION THROUGH LIFE STORIES AND OBSERVATIONS: CASES OF YOUNG EFL TEACHERS IN JAPAN - Masami Yukimori (PUPIL: International Journal of Teaching, Education and Learning, 2025)
The purpose of this study is to explore the professional motivation of young English teachers in Japan through life story interviews and participant observation. In the interviews, key elements of motivation – such as autonomy, competence, and relatedness – were observed. In particular, the ability to conduct lessons autonomously, collaboration with colleagues, and meaningful connections with students emerged as core factors in maintaining high levels of motivation. To deepen the understanding gained from the interviews, participant observations were conducted at each teacher’s school. These observations aimed to examine how each teacher’s motivation was reflected in their daily teaching practices and overall professional life. Rather than remaining internal or abstract, their motivation was visibly expressed through their classroom behaviors, interactions with students, and approaches to instructional tasks.Through this integrated research process, it became evident that the teachers’ professional identity and sources of motivation were rooted not only in their role as English language specialists, but also equally in their identity as caregivers who support students’ holistic development. In the context of Japan’s class teacher system and the emphasis on whole-person education, the broad and complex responsibilities expected of teachers are often considered a factor contributing to the national teacher shortage. Nevertheless, this study found that for some young teachers, these responsibilities – especially the opportunity to build strong relationships with students – served as important sources of motivation.